Pengaruh Perdagangan Internasional terhadap Pertumbuhan Ekonomi di Indonesia - Pasaribu, Alya Sabrina; Nasution, Armin Rahmansyah (Eksis: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
The purpose of this study is to determine and analyze the effect of international trade on economic growth in Indonesia. This study also aims to find out how other factors, such as investment, education, and technology, affect the effect of international trade on economic growth in Indonesia. This research adopts a qualitative approach using document analysis techniques to explore the influence of international trade on Indonesia's economic growth. This study confirms that international trade has a significant and positive influence on economic growth in Indonesia. This is evidenced by the strong positive correlation between real GDP growth and non-oil and gas exports over the period 2010-2020. The contribution of exports to Indonesia's GDP also shows a consistent upward trend, reaching 17.21% in 2020.